The impact of personality on person‐centred care: a study of care staff in Swedish nursing homes. (3rd October 2016) - Elfstrand Corlin, Tinna; Kajonius, Petri J.; Kazemi, Ali
Abstract : Aim and objective: In this study, we explore how personal and situational factors relate to the provision of person‐centred care (PCC) in nursing homes. Specifically, we focus on the relationship between the care staff's personality traits and provision of PCC and to what extent perceptions of the working environment influences this relationship. Background: The ultimate goal of elderly care is to meet the older person's needs and individual preferences (PCC). Interpersonal aspects of care and the quality of relationship between the care staff and the older person are therefore central in PCC. Design and methods: A cross‐sectional Swedish sample of elderly care staff ( N = 322) completed an electronic survey including measures of personality (Mini‐IPIP) and person‐centred care (Individualized Care Inventory, ICI). A principal component analysis was conducted on the ICI‐data to separate the user orientation (process quality) of PCC from the preconditions (structure quality) of PCC. Results: Among the five factors of personality, neuroticism was the strongest predictor of ICI user orientation. ICI preconditions significantly mediated this relationship, indicating the importance of a supportive working environment. In addition, stress was introduced as a potential explanation and was shown to mediate the impact of neuroticism on ICI preconditions. Conclusions: Personality traits have a significant impact on user orientation, and the perception of a supportive and stress free working environment is an important prerequisite for achieving high‐quality person‐centred elderly care. Implications for practice: Understanding how personality is linked to the way care staff interacts with the older person adds a new perspective on provision of person‐centred elderly care.